Pascal's Wager and Information. (9th May 2014) - Schredelseker, Klaus; Breitner, Michael H.; Dunis, Christian; von Mettenheim, Hans-Jörg; Neely, Christopher; Sermpinis, Georgios
ABSTRACT Should we make financial forecasts? The usual answer looks like Pascal's wager: we don't know whether God exists; who erroneously believes loses nothing, who correctly believes wins everything; who correctly disbelieves, gains nothing, who erroneously disbelieves loses everything. Believing is thus a dominant choice. Turned to finance: markets are efficient or not. In an efficient market forecasters and non‐forecasters win nothing; in a non‐ efficient market forecasters win and non‐forecasters lose. Forecasting is rational if inefficiencies have a probability > 0. We use an agent‐based approach in studying the information value in a market with endogenous prices. We show that in inefficient markets rational traders don't make forecasts and an improvement in public information may even be harmful for the users. On average, an investor who has no information (index investor) performs like the market does; it is impossible that all others—those who know more than nothing—perform better. Pascal's wager does not apply. Copyright © 2014 John Wiley & Sons, Ltd.